The single nucleotide polymorphism (SNP) in DNA repair genes by homologous recombination (XRCC2 and RAD51) and the risk of sporadic breast cancer in Poland - Romanowicz, Hanna; Smolarz, Beata; Baszczyński, Jakub; Zadrożny, Marek; Kulig, Andrzej; Góralczyk, Bożena; Połać, Ireneusz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2011)
Background : Single nucleotide polymorphisms in the DNA repair genes have been extensively studied in association with various human cancers such as breast cancer. Material and methods : We investigated an association of polymorphisms in the DNA repair genes XRCC2-Arg188His and RAD51-135G/C with the breast cancer risk. Genotypes were analysed by PCR-RFLP assays in 80 patients with breast cancer and 80 controls. Results : The distribution of the genotypes of XRCC2 Arg188His in both controls and patients did not differ significantly (p > 0,05) from those predicted by the Hardy-Weinberg distribution. The C/C genotype of RAD51 increased the risk of breast cancer occurrence (OR 2.29; 95% PU (0.91–5.72), p = 0.04). Conclusion : G135C polymorphism of the RAD51 gene may be associated with the incidence of sporadic breast cancer in Polish women.